Pemeriksaan dan Penyuluhan Kesehatan Cabang Muhammadiyah Wiradesa Kabupaten Pekalongan - Tuti Suparyati (Lembaga Pengembangan Kinerja Dosen, 2024)
Muhammadiyah, Wiradesa branch, Pekalongan Regency, has a General Health Advisory Council (MPKU). Muhammadiyah is an organization that cares about the condition of society, namely the health condition and economic condition of the community. MPKU holds blood pressure, blood sugar, uric acid, cholesterol and free health education activities. , the location of the activity was centered in one of the Muhammadiyah/Aisyiyah Mayangan Branches, Wiradesa District, Pekalongan Regency. The Wiradesa Branch of the Muhammadiyah Public Health Advisory Council requires medical personnel to participate in carrying out these community service activities. The aim of this community service activity is Early Detection of Non-Communicable Diseases by providing health services in the form of checking blood pressure, blood sugar, uric acid, cholesterol and free health education